Endogenous Glucocorticoid Metabolism in Bone: Friend or Foe - Martin, Claire S.; Cooper, Mark S.; Hardy, Rowan S. (Frontiers in Endocrinology, 2021)
The role of tissue specific metabolism of endogenous glucocorticoids (GCs) in the pathogenesis of human disease has been a field of intense interest over the last 20 years, fuelling clinical trials of metabolism inhibitors in the treatment of an array of metabolic diseases. Localised pre-receptor metabolism of endogenous and therapeutic GCs by the 11β-hydroxysteroid dehydrogenase (11β-HSD) enzymes (which interconvert endogenous GCs between their inactive and active forms) are increasingly recognised as being critical in mediating both their positive and negative actions on bone homeostasis. In this review we explore the roles of endogenous and therapeutic GC metabolism by the 11β-HSD enzymes in the context of bone metabolism and bone cell function, and consider future strategies aimed at modulating this system in order to manage and treat various bone diseases.